Ursolic acid modulates MMPs, collagen-I, α-SMA, and TGF-β expression in isoproterenol-induced myocardial infarction in rats. (July 2019) - Radhiga, T; Senthil, S; Sundaresan, A; Pugalendi, KV
In the present study, the modulatory effect of ursolic acid (UA) on cardiac fibrosis and mitochondrial and lysosomal enzymes activity in isoproterenol-induced myocardial infarction (MI) in rats were examined. Isoproterenol hydrochloride (ISO; 85 mg/kg body weight) was administered subcutaneously for first two consecutive days. ISO-induced MI in rats significantly decreased the activities of mitochondrial tricarboxylic acid cycle enzymes and respiratory chain enzymes while increased the activities of lysosomal glycohydrolases and cathepsins. The expression of matrix metalloproteinase 2 (MMP-2), MMP-9, collagen type I, α-smooth muscle actin (α-SMA), and transforming growth factor-β (TGF-β) were upregulated in ISO-induced MI in rats. UA administration to rats showed increased activities of mitochondrial tricarboxylic acid cycle enzymes and respiratory chain enzymes and decreased activities of lysosomal glycohydrolases and cathepsins in ISO-induced rats. Furthermore, expression of MMP-2, MMP-9, collagen type I, α-SMA, and TGF-β downregulated in UA-administered rats. Thus, our results demonstrate that UA has an anti-fibrotic effect and attenuates the mitochondrial and lysosomal dysfunction in ISO-induced MI in rats.